2019
DOI: 10.1186/s40168-019-0734-2
|View full text |Cite
|
Sign up to set email alerts
|

Stable distinct core eukaryotic viromes in different mosquito species from Guadeloupe, using single mosquito viral metagenomics

Abstract: Background Mosquitoes are the most important invertebrate viral vectors in humans and harbor a high diversity of understudied viruses, which has been shown in many mosquito virome studies in recent years. These studies generally performed metagenomics sequencing on pools of mosquitoes, without assessment of the viral diversity in individual mosquitoes. To address this issue, we applied our optimized viral metagenomics protocol (NetoVIR) to compare the virome of single and pooled Aede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
220
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(256 citation statements)
references
References 71 publications
31
220
5
Order By: Relevance
“…It has been suggested that is maintained in nature through vertical transmission [55]. A recent study has reported that GMV is closely related to Wenzhou sobemo-like virus 4 and Hubei mosquito virus 2 [56]. GMV related virus has been detected only in mosquito sample collected from the field, indicating it is likely acquired horizontally from the environment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that is maintained in nature through vertical transmission [55]. A recent study has reported that GMV is closely related to Wenzhou sobemo-like virus 4 and Hubei mosquito virus 2 [56]. GMV related virus has been detected only in mosquito sample collected from the field, indicating it is likely acquired horizontally from the environment.…”
Section: Resultsmentioning
confidence: 99%
“…The viral genomes contain two segments, encoding an RdRp and one hypothetical protein on segment 1 (1500 - 1600 nt), and a capsid and one hypothetical protein encoded by segment 2 (3000 - 3200 nt). GMV, Wenzhou sobemo-like virus 4 and Hubei mosquito virus 2 are all newly described and currently unclassified viruses with distant relationship to the family Luteoviridae and Sobemoviridae [56].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations